2018
DOI: 10.1140/epjc/s10052-018-5524-7
|View full text |Cite
|
Sign up to set email alerts
|

Linear confinement of a scalar particle in a Gödel-type spacetime

Abstract: Based on the studies of confinement of quarks, we introduce a linear scalar potential into the relativistic quantum dynamics of a scalar particle. Then we analyze the linear confinement of a relativistic scalar particle in a Gödel-type spacetime in the presence of a topological defect. We consider a Gödel-type spacetime associated with null curvature, i.e., the Som-Raychaudhuri spacetime, which is characterized by the presence of vorticity in the spacetime. Then we search for analytical solutions to the Klein-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
111
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 45 publications
(88 reference statements)
7
111
2
Order By: Relevance
“…In summary, we showed that the correct expression for the energy eigenvalues for the case k L = 0 of Ref. [2] can be obtained from an appropriate manipulation of the biconfluent Heun differential equation, in opposition what was concluded in [1]. The results obtained in this comment are consistent with those found in [7].…”
supporting
confidence: 79%
See 2 more Smart Citations
“…In summary, we showed that the correct expression for the energy eigenvalues for the case k L = 0 of Ref. [2] can be obtained from an appropriate manipulation of the biconfluent Heun differential equation, in opposition what was concluded in [1]. The results obtained in this comment are consistent with those found in [7].…”
supporting
confidence: 79%
“…In a recent paper in this Journal, F. Ahmed [1] has pointed out an incorrect expression in [2]. The author has solved the Klein-Gordon equation without interaction in the Som-Raychaudhuri space-time with the cosmic string using the Nikiforov-Uvarov method and obtained the energy eigenvalues and the corresponding eigenfunctions of the system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have studied the physical properties of a series of backgrounds with the Som-Raychaudhuri spacetime. [14] and Vitoria et al have investigated Linear confinement of a scalar particle in a Som-Raychaudhuri space-time [43]. Also, there are a series of backgrounds with the cosmic string in Kerr space-time [44], Schwarzschild space-time [45,46], Gödel-type space-time [40] and AdS space [47].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, let us mention many studies of the Dirac oscillator with topological defects and cosmic string spacetimes in Refs. [28][29][30][31][32][33][34] and analogous investigations for scalar fields in Refs. [35][36][37][38][39].…”
mentioning
confidence: 99%